Can AI Help Me Analyze My Medical Bills? An Academic Perspective on Digital Health and RCM - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2023)
Can AI Help Me Analyze My Medical Bills? An Academic Perspective on Digital Health and RCM The modern healthcare system, while a marvel of scientific ac...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Machine Learning